A framework for estimating immediate interdependent functionality reduction of a steel hospital following a seismic event. (1st August 2018) - Hassan, Emad M.; Mahmoud, Hussam
Highlights: We developed various 2D and 3D finite element models of a steel hospital. We generated fragility functions for all developed models. We devised a framework to compute seismic losses and functionality for a hospital. We used the fragilities for an event to assess losses and functionality reduction. We evaluated the effect of the modeling on the estimated losses and functionality. Abstract: Functionality of an infrastructure is its ability to provide its intended services. Maintaining an acceptable level of infrastructure functionality, particularly for critical infrastructure, following an extreme event is vital for effective community recovery. Estimating functionality depends on proper quantification of losses, which requires accurate assessment of infrastructure damage. The damage is presented in the form of fragility functions that are generally developed using nonlinear finite element analysis. To date, no study has been conducted to assess the effect of modeling approach on seismic fragilities of an infrastructure, the associated losses, and functionality reduction. In addition, existing frameworks for estimating functionality of critical infrastructure, such as a hospital, following an extreme event have not considered the interdependent relationship between a hospital and other lifelines. In this study, a new framework for evaluating immediate functionality of a hospital following an earthquake is presented. The functionality is estimated based on hospital losses that result from its sustained damage as well as damage to other lifelines on which the hospital relies. In addition, the effects of modeling resolution on the calculated fragilities, the estimated direct losses, and the associated functionality are evaluated. The hospital models vary from simplified 2-D with idealized boundary conditions to more comprehensive 3-D models that account for soil-structure interaction. The analysis show that using simplified 2-D models that ignore soil-structure interaction could lead to non-conservative results. On the contrary, using more refined 3-D models could provide accurate estimation of the behavior, and subsequently better assessment of losses and functionality.